Immunoglobulin: unraveling its complex web in aging - Gu, Qiaoli; Wang, Yi; Zhu, Can; Zhou, Xichao; Ni, Li; Zhao, Huan; Yang, Huilin; Shi, Qin (Frontiers in Immunology, 2025)
Aging is a complex biological phenomenon, which involved in a large number of diseases such as cancer, neurodegeneration, and cardiovascular diseases. Understanding the mechanism of aging may facilitate the development of preventive strategies of age-related diseases. Immunoglobulin (Ig) includes proteins with antibody (Ab) activity or membrane-bound proteins that share a chemically analogous structure to Ab. Ig can recognize and neutralize numerous antigens, which constitutes the main characteristic of adaptive immunity. The quantity, glycosylation and function of Ig change with advancing age. Some Ig is found to be accumulated in aged tissues and appear to be regarded as a potential marker for aging, which indicates the critical role of Ig in aging. B cells are main producers of antibodies and undergo aging-related changes, leading to increased autoimmune responses and reduced vaccine responses. The immune dysregulation of B cells is also intensively involved in the alteration of Ig. In this review, we focus on the current research findings on Ig, discuss the relation between Ig and aging, highlight the complex interplay among B cell, gut microbiota, Ig, and aging, and explore potential therapeutic strategy. We hope this review may provide an insight for investigating the regulatory mechanism of Ig in aging, as well as for evaluating the therapeutic potential in treating age-related diseases.